A new cytotoxic steroidal glycoalkaloid from the methanol extract of Blumea lacera leaves - Akter, Raushanara A.; Uddin, Shaikh J.; Tiralongo, Joe; Grice, Darren; Tiralongo, Evelin (© 2015 Canadian Society for Pharmaceutical Sciences, 2016)
This article was published in the Journal of Pharmacy and Pharmaceutical Sciences [© 2015 Canadian Society for Pharmaceutical Sciences] and the definite version is available at: https://ejournals.library.ualberta.ca/index.php/JPPS/article/view/25247/19134